Contributions of collaborative consultation for the inclusion of students with intellectual disabilities - Sandra Lúcia Silva Araújo; Maria Amélia Almeida (Universidade Federal de Santa Maria (UFSM), 2014)
In this article we aim to show the possible contributions of collaborative consultation for the inclusion of students with intellectual disabilities, through a reflective analysis based on relevant literature. In a growing school inclusion process, the entrance of students with intellectual disabilities has represented a significant number not only at school but also in specialized educational services. The inclusion of these students has attracted special attention as well as the necessity to make adjustments and reflections. A contribution in this direction is the practice of collaborative consultation, which can be considered as a partnership between special education teacher, regular teacher and other professionals. The effectiveness of this partnership can bring important contributions to family, school and community. In this sense, collaborative consultation can be an alternative to the inclusion of people with intellectual disabilities, not only in the context of the intervention but also in the prevention, reflection and transformation of the school environment. We seek, therefore, to make some reflections on the subject, based on the literature.